Regulating Secondary Flow in Ultra‐Low Aspect Ratio Microchannels by Dimensional Confinement (Adv. Theory Simul. 4/2018). Issue 4 (16th April 2018) - Shen, Shaofei; Kou, Lisha; Zhang, Xuan; Wang, Defu; Niu, Yanbing; Wang, Jinyi
Abstract : In article number1700034, Yanbing Niu, Jinyi Wang, and co‐workers develop an inertial microfluidic system relative to the deterministic regulation of secondary flows by geometric confinement. The ultra‐low aspect ratio channel containing ordered micro‐obstacles can achieve fluid manipulation in a highly‐efficient manner by helical vortices induced micro‐obstacles in the horizontal, and Dean‐like secondary flow in the vertical plane.